Arterial medial calcification (Mönckeberg’s sclerosis) with chronic renal disease in a zoo-kept Southern tamandua (Tamandua tetradactyla) - Kimura, Tohru (Int J Vet Sci Med, 2021)
Arterial medial calcification observed in animals is equivalent to Mönckeberg’s sclerosis in human beings. This lesion is rarely reported in domestic animals. In addition, little information is available concerning the occurrence of arterial medial calcification in zoo animals. The aim of the current work was to report arterial medial calcification incidentally encountered in a Southern tamandua (Tamandua tetradactyla). This paper described the clinical findings, haematological and serum biochemical profiles, and histopathological results. Haematological examinations showed decreases in white blood cell counts, erythrocytic parameters and platelets. In serum biochemical examinations, both of the creatinine and blood urea nitrogen levels markedly increased in this study. Glucose concentrations dramatically declined from the normal levels to the critical conditions. There was electrolytic imbalance which was not accompanied by increases in calcium and inorganic phosphorus concentrations. Enzyme activities (ALP, AST, ALP, γ-GT, LDH and CK) remarkably increased just before the animal died. Histopathological examinations revealed that this marked and thickened calcification extended linearly around the circumference of the vessels. The calcified deposits were located entirely within the medial layer of the arterial wall. The lesions showed involvement of the internal elastic lamina with calcification. Severe calcification was observed in the glomerular capsules, indicating serious chronic kidney disease. We concluded that arterial medial calcification in the Southern tamandua arose with progressing chronic kidney failure.